Multimode/Multifrequency Low Frequency Airborne Radar Design - Sandra Costanzo; Giuseppe Di Massa; Antonio Costanzo; Antonio Borgia; Claudio Papa; Giovanni Alberti; Giuseppe Salzillo; Gianfranco Palmese; Dario Califano; Luca Ciofanello; Maria Daniele; Claudia Facchinetti; et al. (Journal of Electrical and Computer Engineering)
This work deals with the design of multimode/multifrequency airborne radar suitable for imaging and subsurface sounding. The system operates at relatively low frequencies in the band ranging from VHF to UHF. It is able to work in two different modalities: (i) nadir-looking sounder in the VHF band (163 MHz) and (ii) side-looking imager (SAR) in the UHF band with two channels at 450 MHz and 860 MHz. The radar has been completely designed by CO.Ri.S.T.A. for what concerns the RF and the electronic aspect, and by the University of Calabria for what concerns the design, realization, and test of SAR antennas. The radar has been installed on a civil helicopter and its operation has been validated in flight in both sounder and imager modality. Preliminary surveys have been carried out over different areas of Campania region, South Italy.